Numeric simulation of the solidification of the pure iron varying the solidification process parameters - Mossi, A.; Pariona, M. (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
In the study reported in this work, two-dimensional numerical simulations were made of pure iron solidification in industrial AI 50/60 AFS greensand and mullite molds, using the finite element technique and the ANSYS software program. For this purpose, the thermophysical properties of iron were considered temperature-dependent, while for sand and mullite these properties were considered constant, and the convection phenomenon was also considered on the external surface of the mold. In order to study the influences of the parameters in the solidification process, such as, sand and mullite mold types, preheating temperature of the mold (ambient and heated), superheating temperature of the liquid metal and loss of heat on the mold by convection, the optimization through the factorial design was accomplished. Metallurgical characteristics, such as the attack zone in the feed head and hot top, were not taken into account in this study, since they are irrelevant to the behavior of metal to mold heat transfer. Owing to the temperature-dependent thermo-physical properties of iron, this type of problem is of nonlinear characteristic. The results of the heat transfer are shown throughout the 2D system, as thermal flow, thermal gradient, the cooling curves at various points of the solidified specimen were determined, as well as the analysis of the factorial design of the result and heating or / and cooling in the molds were also accomplished. Through the analysis of the factorial design result of the parameters it was found which mold type influences negatively the result and the interaction of the metal temperature with the convection phenomenon contributed significantly to the result. The cooling curves characterize the grain size and mechanical properties of metal; hence, owing to the smaller grain size of metal cast in mullite molds, this type of mold grants better mechanical properties to the cast part.